The Effect of Using the WhatsApp Digital Application on the Work Effectiveness of Polewali Mandar District Tourism Office Employees - Ihsan, Ahmad ihsan; Anwar; Haeruddin, M. Ikhwan Maulana (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Ahmad Ihsan (2022) "The Effect of Using the WhatsApp Digital Application on the Work Effectiveness of Polewali Mandar District Tourism Office Employees". Supervised: Anwar and M. Ikhwan Maulana Haeruddin. This study aims to find out how the influence of the use of the WhatsApp digital application on the work effectiveness of Polewali Mandar District Tourism Office Employees. The population in this study were employees who worked at the Polewali Mandar Regency Tourism Office and a sample of 34 employees, using a saturated sample formula. Data collection was carried out using a questionnaire method. The data analysis technique used is simple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that the variable significance value of using the WhatsApp digital application is 0.000, this value is smaller than the significance value of 0.05. So that it can be said that the use of the WhatsApp digital application has a positive and significant influence on the work effectiveness of Polewali Mandar District Tourism Office Employees.